Intimate partner violence in Spain (1975-2006) - Wheeler, Duncan (Cuestiones de Género: de la igualdad y la diferencia, 2008)
In this article, I examine how gender-based violence has been framed in Spanish legal, social and cultural discourses since the fall of the dictatorship. Prior to 1997, far less attention was paid to intimate partner abuse than in most other democratic states. In the last ten years, this situation has been reversed. There has been heavy media coverage, and new legislation that adopts an holistic approach to the problem. I will attempt to place these changes in context and to provide extensive bibliographical information for those readers seeking information in more specialised fields.